Descriptions of Animals on Example of Lion in Philippe de Thaon’s Bestiary - Makowski, Łukasz (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
Philippe de Thaon was a clerc, who worked in first quarter of XII century. He had left texts about nature science, in which must be distinguish 1st French-language bestiary. This source – Livre des bastiaires – was compared with earlier texts, which were sources of information for author – Physiologus in various version (greek, latin, BIs- supplemented by part of Isidore of Seville’s Etymologiae) and Etymologiae of Isidore of Seville. These sources was popular in Middle Ages, and all had been written in beginning centuries of Christianity. Lion is first animal in all of these sources. Sources, generally, presenting positive image of king of animal. They containing also the same describing, like, f. ex. sleeping with an opening eyes. Simultaneously authors of every later sources added a new elements to behavior or look, wherein Philippe de Thaon made the most detailed description. In symbolical aspects also it is looked a changes, althought preserving simile tradition of describing. Evolution of that aspect was similar like in physical description. Etymologiae in an unusual source, because author had not written symbolical explanation of animals.